Effects of Cross-linker Variation on Swelling Behavior of Hydrogels - Iqubal, Dr. S. M. Shakeel (Asian Journal of Pharmaceutics (AJP), 2020)
Introduction: The main objective of this study is to find the effects of cross-linker variation on swelling behavior of hydrogels at different temperatures, that is, 30 minâ€“120 min. Hydrogels are three-dimensional cross-linked structural arrangement of the polymeric materials with the ability to absorb huge amounts of water while maintaining their dimensional stability. Materials and Methods: A solution of 20% glutaraldehyde (GA) was prepared in 100 ml standard flask by dissolving 20.0 g GA in a standard flask (of capacity 100 ml) and make up the volume up to the mark using demineralized water (DMW). The gelatin-polyethylene glycol (PEG) composite hydrogels were prepared by simultaneous method, in which all the constituent component networks are polymerized concurrently. Different combinations of gelatin-PEG composite hydrogels were prepared with methylene blue (MB) dye in it. Swelling was studied with the help of the following equation: dssdW-WI=Ã—100W Results and Discussion: The observation showed that the decrease in the absorbance of MB release through the sample membrane may be due to the contraction of the microvoids formed between the polymeric chains. Conclusion: Based on our results which conclude that with increasing crosslinking agent from 5 ml to 15 ml, swelling ratio of the prepared sample decreased from 473.83 to 428.97 in DMW due to the decrease in the pore diameter of the sample. As a result, more and more solvent diffuses into the matrix and produce gel with increased swelling ratio.